Identification and Validation of Reference Genes for Gene Expression Analysis in Different Development Stages of Amylostereum areolatum - Fu, Ningning; Li, Jiaxing; Wang, Ming; Ren, Lili; Zong, Shixiang; Luo, Youqing (Frontiers in Microbiology, 2022)
A strict mutualistic relationship exists between the Sirex noctilio and the Amylostereum areolatum carrying and spreading by its partner. The growth and development of this symbiotic fungus is the key to complete the life history of the Sirex woodwasp. Real-time quantitative polymerase chain reaction (RT-qPCR) is used to measure gene expression in samples of A. areolatum at different growth stages and explore the key genes and pathways involved in the growth and development of this symbiotic fungus. To obtain accurate RT-qPCR data, target genes need to be normalized by reference genes that are stably expressed under specific experimental conditions. In our study, the stability of 10 candidate reference genes in symbiotic fungal samples at different growth and development stages was evaluated using geNorm, NormFinder, BestKeeper, delta Ct methods, and RefFinder. Meanwhile, laccase1 was used to validate the stability of the selected reference gene. Under the experimental conditions of this study, p450, CYP and γ-TUB were identified as suitable reference genes. This work is the first to systematically evaluate the reference genes for RT-qPCR results normalization during the growth of this symbiotic fungus, which lays a foundation for further gene expression experiment and understanding the symbiotic relationship and mechanism between the S. noctilio and A. areolatum.